Towards a conceptual model of crisis communication with the media in the financial sector - Juliette Kathryn MacLiam; Rachel Barker (Communicare)
Although crisis communication has emerged as a specialised study field for public relations scholars and practitioners and has been a mounting area of inter-disciplinary research in recent years, several gaps in current literature on crisis communication exist. Gaps include a notable focus on the planning, prevention and recovery stages with lesser attention being devoted to the crisis-response stage; a lack of a comprehensive conceptual framework to guide communication decision makers during this critical period; and that crisis-communication studies appear to be predominantly Western based. This article attempts to address these gaps by focusing on the crisis-response stage, with particular emphasis on communication with the media during a crisis. It is acknowledged that the success of a crisis-management effort is profoundly affected by what an organisation says and does during a crisis – termed the crisis response (Benoit, 1997; Coombs, 2004). This article focuses on this crisis response and is divided as follows: firstly, an introduction to key terminology is provided, followed by the theoretical background, the research approach and methodology, as well as the findings from the case studies, which culminate in the proposed conceptual model for effective crisis communication with the media. Lastly, a critical evaluation of the model is presented and recommendations for further research are provided.